Language Policy at the Federal University of Amazonas - Simas, Hellen Cristina Picanço; Miranda, Débora dos Santos de (Revista Aval, 2025)
The aim of this research was to discuss language policy at the Federal University of Amazonas (UFAM) and identify what actions have already been implemented since its creation in 2018. To generate the data, we selected the methodological steps of documentary and field research, interviewing UFAM course coordinators and indigenous students from the Institute of Social Sciences, Education and Zootechnics (ICSEZ), and using a qualitative approach to analyze them from the theoretical framework on language policy. The results show that, since the publication of Resolution no 28/2018, which covers language policy at the university, there have been no real changes.